Mechanical and tribological properties of V–C–N coatings as a function of applied bias voltage - Caicedo, J.C.; Gonzalez, R.; Caicedo, H.H.; Gholipourmalekabadi, M.; Amaya, C. (Сверхтвердые материалы, 2016)
The aim of this work is to determine the mechanical and tribological behavior of V–C–N coatings deposited on industrial steel substrates (AISI 8620) by using carbon–nitride coatings as a protective materials.